Printing and erasing of DNA-based photoresists inside synthetic cells [research data] - Göpfrich, Kerstin; Walther, Tobias (Universität, 2022)
In the pursuit to produce functioning synthetic cells from the bottom up, DNA nanotechnology has proven to be a powerful tool. However, the crowded yet highly organized arrangement in living cells, bridging from the nano- to the micron-scale, remains challenging to recreate with DNA-based architectures. Here, laser microprinting is established to print and erase shape-controlled DNA hydrogels inside the confinement of water-in-oil droplets and giant unilamellar lipid vesicles (GUVs). The DNA-based photoresist consists of a photocleavable inactive DNA linker which interconnects Y-shaped DNA motifs when activated by local irradiation with a 405 nm laser. An alternative linker design allows to erase custom features from a preformed DNA hydrogel with feature sizes down to 1.38um. The present work demonstrates that the DNA hydrogels can serve as an internal support to stabilize non-spherical GUV shapes. Overall, DNA-based photoresists for laser printing in confinement allow to build up architectures on the interior of synthetic cells with light, which diversifies the toolbox of bottom-up synthetic biology.